Cause, classification of voltage sag, and voltage sag emulators and applications : a comprehensive overview - Han, Yang (2021)
The large-scale application of wind power and photovoltaic power solves the energy crisis and alleviates the environmental problems caused by the use of conventional energy. However, they are at risk of being randomly tripped from the network when faced to voltage sag and severe fault events, which will lead to a sudden reduction of active power output and also complicates fault recovery process of the whole system. Moreover, it may also aggravate failures and lead to large-scale power outages, which stimulates a growing interest in analyzing the low-voltage ride-through (LVRT) capabilities of the renewable energy systems (RES) and improving the performance through developing various mathematical models and analysis tools. In this paper, a systematical overview of cause, classification of voltage sag phenomena and voltage sag emulating techniques is presented, and four voltage sag generators (VSGs) are discussed and compared, which include generator based-VSG, shunt impedance based-VSG, transformer based-VSG and full converter based-VSG. Furthermore, a closed-loop detection platform based on real-time digital simulator (RTDS) for the converter controller of a permanent magnet synchronous generator (PWSG) set is introduced, to investigate the LVRT performance of the WT system under grid voltage sag conditions. Finally, the application of VSG in RES are presented and the future research directions are also discussed.